(untitled) (Nigerian Journal of Technology, 2022)
The DFIG is a type of induction machine which has been serving extensively in the WEC system. Many researchers have worked on the DFIG and its integration to the grid system, proposed control schemes and designs for the DFIG. However, there have not been a comprehensive critical review on the contemporary issues related to the DFIG. This paper presents a critical review of the contemporary issues related to DFIG. The research findings of this paper are the issues related to the DFIG ranging from the unbalanced voltage dip which results to an induction of very large torque pulsations and DC ripples in the rotor circuit; the preferences and relativities on which control strategy is best for the DFIG considering the FOC and the DTC control schemes, and down to the LVRT issues. The contemporary issues relating to the DFIG operation and their effects on the DFIG operation are also discussed.